AICAAD : artificial intelligent CAAD : an approach to integrate artificial intelligent features in CAAD - 176754 Chang, Chee Choon (Skudai : Universiti Teknologi Malaysia, 2006)
Topical Study (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2006